Flexible work contract in the Saudi labor Low - Nasser Abdullah Ayed Al-Qahtani (International Journal of Law Research and Studies, 2025)
This research discussed the flexible work contract as one of the most important types of work contracts in the Saudi Law, which many employers resort to cover the need for work that does not require long contracts or full working hours. The contract is flexible, and the wage is based on the hour without commitment to any other obligations, and the worker can contract this contract as an additional source of income without conflicting with his original work, and this research reviews the provisions of the flexible work contract. The research dealt with the provisions and controls of the flexible work contract in light of the Saudi labor Law and its executive regulations. This research was divided into an introductory section and two main sections. In the introductory section, I discussed the nature of flexible work, in the first section I discussed the provisions of flexible work, and in the second section I discussed the implications of the flexible work contract. The study produced many results, the most important of which is the employment contract with a flexible work system that is characterized by several provisions for the worker, including: that the worker is not subject to a trial period, and the working hours for a worker with one employer must not exceed more than 95 hours per month, and the worker has the right to refuse work if the employer requests it. Work for this without the right to take any action against him. As for the employer, it is distinguished that the worker is not entitled to an end-of-service reward and is not entitled to any type of leave or compensation for it. I have also reached a number of recommendations, the most important of which is considering amending Article Two of the Labor Law by adding the definition of flexible work and signing out an article in the Labor Law that regulates the provisions and flexible working rules.